Model Strengthening Spiritual Quotient through Wayang Kekayon Khalifah in Islamic Religious Education Learning - Hidayat, Kun (PT. Student Rihlah Indonesia, 2025)
This study examines the integration of Wayang Kekayon Khalifah into Islamic Religious Education (IRE) learning to enhance students' spiritual quotient. The primary issue addressed is the lack of connection between religious values and local wisdom in formal education. This research aims to analyze the benefits of using wayang as a medium for internalizing religious and moral values based on Javanese culture. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation at SMAN 5 Puspanegara Yogyakarta. The findings indicate that this integration combines Islamic preaching narratives with local cultural symbols, enabling students to understand religious teachings contextually and reflectively. Its implications enrich learning experiences, strengthen religious character, and shape spiritual awareness aligned with students’ cultural identity.